2003
DOI: 10.1073/pnas.0634629100
|View full text |Cite
|
Sign up to set email alerts
|

Protein pathway and complex clustering of correlated mRNA and protein expression analyses in Saccharomyces cerevisiae

Abstract: The mRNA and protein expression in Saccharomyces cerevisiae cultured in rich or minimal media was analyzed by oligonucleotide arrays and quantitative multidimensional protein identification technology. The overall correlation between mRNA and protein expression was weakly positive with a Spearman rank correlation coefficient of 0.45 for 678 loci. To place the data sets in a proper biological context, a clustering approach based on protein pathways and protein complexes was implemented. Protein expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
227
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(247 citation statements)
references
References 44 publications
18
227
2
Order By: Relevance
“…However, it was recently shown that protein expression is transcriptionally controlled for some entire protein pathways such as purine and pyrimidine nucleotide biosynthetic pathways and pathways for amino acids such as methionine (49). This corresponds with our findings for the purine and pyrimidine metabolism where the four proteins found to have changed expression in this part of the metabolism also were identified as changed on the transcriptional level.…”
Section: Discussionsupporting
confidence: 91%
“…However, it was recently shown that protein expression is transcriptionally controlled for some entire protein pathways such as purine and pyrimidine nucleotide biosynthetic pathways and pathways for amino acids such as methionine (49). This corresponds with our findings for the purine and pyrimidine metabolism where the four proteins found to have changed expression in this part of the metabolism also were identified as changed on the transcriptional level.…”
Section: Discussionsupporting
confidence: 91%
“…Among the 74 proteins enriched in GC described in the previous section, 15 are represented on the microarray, and nine transcripts were identified as enriched in GC (supplemental Table 2). These results confirm the general observation that mRNA levels are not always consistent with protein levels because of post-transcriptional, translational, or post-translational regulations (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). They also highlight the importance of proteomics analysis.…”
Section: Comparative Analysis Of Transcriptome Data and Proteome Data-supporting
confidence: 76%
“…By focusing our microarray data analysis on proteins significantly enriched at the TC surface, we focused our analysis on the putative primary source of disease in PE, the trophoblast and effectively only included microarray probes validated at the level of protein expression. Numerous genes are regulated by post-transcriptional and post-translational mechanisms and as such the array signal for the mRNA may not directly correlate with protein expression levels (17,51,52).…”
Section: Discussionmentioning
confidence: 99%